2007
DOI: 10.1093/jn/137.12.2747
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity Is Highly Prevalent and Predicts Underweight but Not Overweight in Adults and School Children from Bogotá, Colombia , ,3

Abstract: The aims of this study were to determine the sociodemographic and dietary correlates of household and child food insecurity in Bogotá, Colombia and to examine whether food insecurity is a risk factor for underweight or overweight in this population. We analyzed data from 2359 families with 2526 children 5-12 y of age who completed a cross-sectional survey conducted in 2006. The survey was representative of low- and middle-income families who had children enrolled in the public primary school system of Bogotá. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
106
11
18

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(159 citation statements)
references
References 41 publications
24
106
11
18
Order By: Relevance
“…Confirming those of other studies (7,13,22,(30)(31)(32)(33) , the results of the present study showed that food insecurity is negatively associated with household economic status indicators. The findings of a study on Iranian households also showed that food insecurity was inversely related to household economic status (size of home), in urban areas, but not in rural areas (14) .…”
Section: Discussionsupporting
confidence: 92%
“…Confirming those of other studies (7,13,22,(30)(31)(32)(33) , the results of the present study showed that food insecurity is negatively associated with household economic status indicators. The findings of a study on Iranian households also showed that food insecurity was inversely related to household economic status (size of home), in urban areas, but not in rural areas (14) .…”
Section: Discussionsupporting
confidence: 92%
“…It is important to note that the mean BMI was within the normal weight range, while the fat percentages related to the classification "below average" (but not malnutrition), unlike several studies that have indicated an association between FI and malnutrition 16,17 . Thus, the present study demonstrated that there is a greater chance that male CC users in Brazil who are in a situation of severe food insecurity will present lower weight and fat percentages than those in a situation of food security.…”
Section: Discussionmentioning
confidence: 68%
“…Some studies have shown a relationship between food insecurity and anthropometric and nutritional indicators for overweight and obesity [13][14][15] , while other studies have presented data showing significant associations between food insecurity and malnutrition and nutrient deficiency 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Details of the study designed have been reported earlier (Isanaka et al, 2007). In brief, we selected a representative sample of 3202 primary school children of age 5-12 years from 3032 households, using a cluster sampling strategy in which all primary school grades 1-5 of all 361 public schools in the city were included.…”
Section: Study Populationmentioning
confidence: 99%